Increasing rates of long-term nitrogen deposition consistently increased litter decomposition in a semi-arid grassland - Hou, Shuang-Li; Hättenschwiler, Stephan; Yang, Jun-Jie; Sistla, Seeta; Wei, Hai-Wei; Zhang, Zhi-Wei; Hu, Yan-Yu; Wang, Ru-Zhen; Cui, Shu-Yan; Lü, Xiao-Tao; Han, Xing-Guo (The New phytologist, 2021)
• The continuing nitrogen (N) deposition observed worldwide alters ecosystem nutrient cycling and ecosystem functioning. Litter decomposition is a key process contributing to these changes, but the numerous mechanisms for altered decomposition remain poorly identified. • We assessed these different mechanisms with a decomposition experiment using litter from four abundant species (Achnatherum sibiricum, Agropyron cristatum, Leymus chinensis and Stipa grandis) and litter mixtures representing treatment-specific community composition in a semi-arid grassland under long-term simulation of six different rates of N deposition. • Decomposition increased consistently with increasing rates of N addition in all litter types. Higher soil manganese (Mn) availability, which apparently was a consequence of N addition-induced lower soil pH, was the most important factor for faster decomposition. Soil C : N ratios were lower with N addition that subsequently led to markedly higher bacterial to fungal ratios, which also stimulated litter decomposition. • Several factors contributed jointly to higher rates of litter decomposition in response to N deposition. Shifts in plant species composition and litter quality played a minor role compared to N-driven reductions in soil pH and C : N, which increased soil Mn availability and altered microbial community structure. The soil-driven effect on decomposition reported here may have long-lasting impacts on nutrient cycling, soil organic matter dynamics and ecosystem functioning.